Chronic psychosocial stress reveals Alzheimer’s disease in a novel at-risk rat model - A. Alkadhi, Karim (Journal of Contemporary Medical Sciences, 2023)
Extensive individual variations in the time of onset and severity of the sporadic type of Alzheimer’s disease (AD), may be due to some patient-related external factors. Stress is increasingly recognized as an external factor in the development of AD. Several labs, including mine, have demonstrated that chronic stress or corticosterone administration aggravates the disease in both transgenic and non-transgenic animal models. We have developed a novel rat model that simulates seemingly normal individuals who are predisposed to develop AD. This review summarizes the findings we have reported on the effect of chronic psychosocial stress in this at-risk model of AD. Behavioral (learning and memory tests), electrophysiological (evoked long-term potentiation) and molecular (protein levels of memory-related signaling molecules a well as AD-related molecules. Our findings suggest that even mild psychosocial stress noticeably transforms this seemingly normal rat model to a full-fledge AD phenotype.